NanoTag is an improved method to map interactions between DNA and proteins not requiring IgG - Maria A. Dimitriu; Rodrigo G. Arzate-Mejía; Leonard C. Steg; Pierre-Luc Germain; Isabelle M. Mansuy (Scientific Reports)
Abstract Genome-wide profiling of DNA–protein interactions in cells can provide important information about mechanisms of gene regulation. Most current methods for genome-wide profiling of DNA-bound proteins such as ChIP-seq and CUT&Tag use conventional IgG antibodies to bind the target protein(s). This limits their applicability to targets with available high affinity and specificity antibodies and prevents their use for other targets. Here we describe NanoTag, an IgG-free method derived from CUT&Tag to profile DNA–protein interactions. NanoTag is based on a fusion between an anti-GFP nanobody and Tn5 transposase that can map GFP-tagged proteins associated with chromatin in a fast, cost-effective and animal-free manner. We used NanoTag to indirectly profile the histone mark H3K4me3 genome-wide via its binding partner TATA box-binding protein-associated factor 3 (TAF3) and the transcription factors Nanog and CTCF in mouse embryonic stem cells (mESCs). NanoTag results show high inter-replicate reproducibility, high signal-to-noise ratio and strong correlation with CUT&Tag datasets, validating its accuracy and reliability. NanoTag provides a novel, flexible and cost-effective IgG-free method to generate high resolution DNA-binding profiles in cells and tissues.